Purebelle beauty spa salon / Nur Nahdatul Nadia Rely … [et.al.] - Rely, Nur Nahdatul Nadia; Douglas, Jonathan Jilum; Joharie, Nor Fadila; Azhar, Nur Atiqah Nabilah; Derahman, Ain Umairah (2014)
Our business is called PureBelle Beauty Spa Salon because we provide a service which is universal for women from head to toe and implement methods to provide relaxation elements and it is specifically for women only when doing spa in our premise and for those who is love are doing beauty. We combining spa and salon in one time in our business so it can make women easier to do what treatment and services they want without go one place to another place to get different the services.